(untitled) (Ameghiniana, 2014)
Twelve ostracod species are identified from Cerro de la Gloria and Canal 18 Members which, in the analysed locality, have been found for the first time superimposed, although separated by a discontinuity. Las Escobas Formation has been deposited in a marginal marine environment; the Cerro de la Gloria Member indicates partially restricted environmental conditions such as a slightly hypohaline lagoon of decreasing energy; the Canal 18 Member was environmentally restricted, with hypoxic conditions, otherwise evidences of increasing environmental energy are registered. Lithology and taphonomic features of macrofossils indicate cycIical altemations of increasing-decreasing water energy.